Impact of inflation on consumers’ spending pattern / Jelani Razali, Nurhani Aba Ibrahim and Khalik Ibrahim - Razali, Jelani; Aba Ibrahim, Nurhani; Ibrahim, Khalik (2010)
Inflation affects the standard of living of most households, especially the lower income group. This paper sheds light on the effect of the current inflation on the urban poor household spending pattern and how they cope with the increasing cost of living. There were 219 respondents in ten areas in Kuching City and Samarahan surveyed in this study. The majority (69.4%) of the poor households were private sector employees and self-employed households. The findings revealed that inflation had seriously affected the consumer’s expenditure on food (68.9%), utility (42.0%), education (35.2%), housing (30.1%), and the least affected was vacation expenses (4.6%). The consumers coped with the rising food prices by buying cheaper products (87.2%), cutting expenditure on other items (82.6%), rationing on food expenditure (72.2%) and replacing certain food with other alternative (53.0%).